MOTION GRAFIS SEJARAH JEMBATAN RATAPAN IBU PAYAKUMBUH SUMATERA BARAT - Satria Antomi; Zubaidah A Zubaidah A (DEKAVE : Jurnal Desain Komunikasi Visual, 2021)
Payakumbuh has historical events. Among the historical events that occurred in the city of  Payakumbuh called the Ratapan Ibu bridge. The bridge is one proof of the history of struggle in West Sumatra, especially in Payakumbuh City. Lack of public appreciation for historical stories and evidence of historical heritage of the Ratapan Ibu bridge. This causes the later generations to know less about the story and care less about its historical evidence. It is necessary to re-communicate these historical events to the public, through motion graphics. The advantage ofmotion graphicscombination is aof illustration, typography, photography, video and audio using animation techniques.The design method used is the 4D (design methodfour-D)using 4 design stages, namely define, design, development, and disseminate. Sources of data used in this design are in the form of statements about the tools, properties, conditions and specific activities concerned.The design results in the form of motion graphics that have stories, pictures, and audio, can make today's young generation learn local history, so that its sustainability can be maintained. The motion graphic of thehistory of the Ratapan Ibu bridge is supported by supporting media in the form of mugs, billboards, tote bags, Youtube, Instagram, twitter and facebook, which are able to promote the Motion Graphic of the History of the Ratapan Ibu Bridge.Keywords: Motion Graphic, History, Mother's Lamentation Bridge,Payakumbuh